A TOPSIS–AHP-Based Approach for Outsourcing Service Provider Selection: A Case Study in the Automotive Industry - Quispe-Atanacio, Willy; Moore-Torres, Karol; Rosales-López, Pedro; Tinoco-Gomez, Oscar; Salas-Bacalla, Julio (Journal of Ecohumanism, 2026)
El This study addresses supply chain management in the automotive industry, a highly competitive sector in which outsourcing plays a critical role in cost reduction and operational flexibility. A representative case involves the subcontracting of cardboard box manufacturing for glass packaging, whose efficiency directly affects production performance. To optimize supplier selection, a hybrid multicriteria decision-making (MCDM) approach integrating the Analytic Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS) was applied. AHP was employed to determine the relative weights of the evaluation criteria through pairwise comparisons, while TOPSIS was used to rank suppliers based on their relative closeness to the ideal solution, incorporating both quantitative and qualitative factors. The methodology was implemented in a real-world automotive case study, assessing cardboard packaging suppliers according to four key criteria: unit cost, quality, delivery time, and environmental sustainability. The integration of expert judgment with verifiable technical data ensured a robust and objective evaluation of the available alternatives. The results revealed that, among the shortlisted candidates, the selected supplier emerged as the most favorable option. This supplier demonstrated a competitive unit cost and acceptable delivery time, despite exhibiting comparatively lower performance in environmental sustainability. This finding highlights the necessity of balancing organizational priorities in accordance with economic and operational constraints. In conclusion, the study demonstrates that the application of multicriteria decision-making methods (AHP–TOPSIS) constitutes an effective decision-support tool for supplier selection, enabling improved operational efficiency and enhanced competitiveness within the automotive supply chain.